Does compulsion explain addiction?: opinion - Heinz, Andreas; Gutwinski, Stefan; Bahr, Nadja Samia; Spanagel, Rainer; Di Chiara, Gaetano (Addiction biology, 2024)
One of the leading drug addiction theories states that habits and the underlying neural process of a ventral to dorsal striatal shift are the building blocks of compulsive drug-seeking behaviour and that compulsion is the maladaptive persistence of responding despite adverse consequences. Here we discuss that compulsive behaviour as defined primarily from the perspective of animal experimentation falls short of the clinical phenomena and their neurobiological correlates. Thus for the human condition, the concept of compulsive habits should be critically addressed and potentially revised.
Erstmals veröffentlicht: 08. April 2024
Gesehen am 28.01.2025